2018
DOI: 10.1038/s41598-018-20836-w
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wnt signaling in dopamine containing neurons is associated with pathogenesis in a rotenone triggered Drosophila Parkinson’s disease model

Abstract: Parkinson’s disease, which is the one of the most common neurodegenerative movement disorder, is characterized by a progressive loss of dopamine containing neurons. The mechanisms underlying disease initiation and development are not well understood and causative therapies are currently not available. To elucidate the molecular processes during early stages of Parkinson’s disease, we utilized a Drosophila model. To induce Parkinson’s disease-like phenotypes, we treated flies with the pesticide rotenone and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 68 publications
1
34
0
1
Order By: Relevance
“…A further potential connection with regards to the above is pesticides' potential suppression of the Wnt/β-catenin signaling pathway [106][107][108]. Paraquat exposure altered the levels of the Wnt pathway genes in mouse neural progenitor cells [106], rotenone impaired Wnt signaling in a Drosophila PD model [107] and Deltamethrin also reduced Wnt signaling pathway genes in zebrafish's development of swim bladder [108]. Wnt signaling is known to be impaired in AD [109][110][111], and activation of the Wnt/β-catenin signaling pathway represses BACE-1 expression [112].…”
Section: Enhancement Of Aβ and Tau Expression Modification And Clearmentioning
confidence: 99%
“…A further potential connection with regards to the above is pesticides' potential suppression of the Wnt/β-catenin signaling pathway [106][107][108]. Paraquat exposure altered the levels of the Wnt pathway genes in mouse neural progenitor cells [106], rotenone impaired Wnt signaling in a Drosophila PD model [107] and Deltamethrin also reduced Wnt signaling pathway genes in zebrafish's development of swim bladder [108]. Wnt signaling is known to be impaired in AD [109][110][111], and activation of the Wnt/β-catenin signaling pathway represses BACE-1 expression [112].…”
Section: Enhancement Of Aβ and Tau Expression Modification And Clearmentioning
confidence: 99%
“…A recent study by Stephano et al [ 71 ] showed that chronic exposure to 500 µM rotenone does not cause a significant DA neuron loss for at least up to 10 days, whereas the climbing ability declines from day 6 onwards. They took advantage of the absence of neuronal loss and isolated DA neurons after 3 days of rotenone treatment, the timepoint considered to be the presymptomatic phase, and analyzed their transcriptome.…”
Section: Chemically Induced Models Of Sporadic Pdmentioning
confidence: 99%
“…We found evidence for shared functional processes and pathways among DEGs in these two models. Among upregulated genes, strong enrichment occurred in biological processes related to Wnt signaling pathway, transcription regulation, cilia functions, and estradiol responses, all of which have previously been shown to be associated with PD dysfunctions (Gonzalez-Reyes et al, 2012;Siani et al, 2017;Stephano et al, 2018). For example, impaired Wnt signaling in DAergic neurons has been associated with pathogenesis in a rotenone-triggered PD model (Stephano et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Among upregulated genes, strong enrichment occurred in biological processes related to Wnt signaling pathway, transcription regulation, cilia functions, and estradiol responses, all of which have previously been shown to be associated with PD dysfunctions (Gonzalez-Reyes et al, 2012;Siani et al, 2017;Stephano et al, 2018). For example, impaired Wnt signaling in DAergic neurons has been associated with pathogenesis in a rotenone-triggered PD model (Stephano et al, 2018). Loss of cilia will decrease the ability of cholinergic neurons to respond to a sonic hedgehog signal that triggers neuroprotective signaling toward DAergic circuits (Gonzalez-Reyes et al, 2012).…”
Section: Discussionmentioning
confidence: 98%